Tuning of polarization, internal electric field, and hysteresis loop behaviours in BaTiO3/BaxSr1-xTiO3 superlattices - Lim, Kok Geng; Chew, Khian Hooi (AIP Publishing, 2018)
A thermodynamic model based on the Landau-Ginzburg theory is developed to study the polarization and hysteresis loop behaviors in ferroelectric superlattices with technologically important BaxSr1-xTiO3 (BST) solid solutions. Our study shows that the polarization, coercive field, and hysteresis loop behaviors can be tailored by changing the thickness ratio and the Ba/Sr content of BST. The study also found that the sign of the internal fields depends sensitively on both thickness ratio and Ba/Sr content of BST. Both results imply that the internal electric field of superlattice can be tuned to yield zero polarizing or depolarizing field via manipulation of thickness ratio and composition. These findings could pave the way to enhance the efficiency of ferroelectric photovoltaic devices by manipulating the internal electric field through thickness and composition.